Aspek Luar Owaadaa Orang Mee - Goo, A. Andreas (Universitas Cenderawasih, 2023)
This research aims to analyze the external aspects of Owaadaa in the Mee Tribe. The research method used is qualitative with a descriptive approach. This research was conducted in Tuwaida Village, Kamuu Selatan District, Dogiyai Regency, Central Papua Province. The data collection techniques used were observation, interview, and literature study. Research informants are Mee traditional leaders who have in-depth and broader knowledge about the culture of the Mee people. The data analysis technique used is ethnographic analysis. Ethnographic analysis technique is used to describe the culture as it is related to owaadaa. The results show that Owaadaa is the center of orientation for the Mee people. Owaadaa was founded in the maki okogoo which is also in anthropological terms called a community or indigenous village in the present time. Owaadaa must be owned by each nucleus family as it affects the physical and spiritual health of family members. In maki okogoo there are yame kopaa clan and clan api kopaa. Both kinds of clans are bound to have an owaadaa, but the api kopaa clans have to establish an owaadaa in the land of their ancestors' inheritance called didee makii.